Human Trafficking Perspektif Al-Qur'an: Tinjauan Hermeneutika Maʿnā-cum-Maghzā - Khoiroti; Delta Yaumin Nahri (Nun: Jurnal Studi Alquran dan Tafsir di Nusantara, 2022)
Human trafficking is one of the world's problems that almost every country, including Indonesia, experiences or faces. Human trafficking is not a new issue in Indonesia, as this practise has never ceased to exist throughout the years. Humans are viewed as commodities that can be easily exploited, whereas, according to Islam, humans must be protected and granted freedom in accordance with their nature. Therefore, it is necessary to conduct a comprehensive analysis of human trafficking in the Qur'an so that it can be implemented in practise. This research asks how the ma'nā-cum-maghzā study in Q. Yūsuf [12]: 19-20 relates to human trafficking. As a result, this paper employs the analytical-critical method and Sahiron Syamsuddin's ma'nā-cum-maghzā theory as its methodology and focuses solely on Q. 12: 19-20. Human trafficking is not explicitly forbidden in the Qur'an, but it is described in the form of the story of the past. In the story of the Prophet Yūsuf (peace be upon him), he was a victim of human trafficking. This practise violates the right to liberty of every human being, so it is imperative that countries abandon it.